Peran Literasi Baca Tulis Dalam Menumbuhkan Minat Membaca Siswa di Madrasah Tsanawiyah Negeri - Mhd Rizkiy Bahar Siregar; Annisa Dahlila Angelina; Maisarah Maisarah; Liza Annisa; Mardianto Mardianto; Haidir Haidir (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
The School Literacy Movement (GLS) which is being promoted by the MTsN 2 Medan school which aims to increase students' interest in books, even if it is only a sheet and frees them to read any book. However, not all students are enthusiastic about reading literacy, even though the school has made extracurriculars based on reading and writing. The research method used was descriptive research using a survey approach. The subjects studied were all students at MTsN 2 Medan from grades VI, VII, XI, however, it was narrowed down to 30 people, with 10 samples taken at each grade level. Collecting data in the study was carried out by interview, observation, and documentation methods. The data obtained in this study were then analyzed using qualitative descriptive analysis and focused on using the Miles & Huberman model which consisted of data reduction, presentation, and conclusion. The results of the analysis of this study indicate that the reading literacy activities carried out by MTsN 2 Medan schools provide good results and the growing interest in reading and writing of students. 'an. And the school also makes every class and corner of the school in the form of slogans that are easy for students to read and each class is provided with bookshelves that make it easier for students to read.